2017
DOI: 10.1007/s11067-017-9348-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Accessibility using Big Data: The Role of the Changing Conditions of Network Congestion and Destination Attractiveness

Abstract: Accessibility is essentially a dynamic concept. However, most studies on urban accessibility take a static approach, overlooking the fact that accessibility conditions change dramatically throughout the day. Due to their high spatial and temporal resolution, the new data sources (Big Data) offer new possibilities for the study of accessibility. The aim of this paper is to analyse urban accessibility considering its two components -the performance of the transport network and the attractiveness of the destinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 41 publications
2
72
0
6
Order By: Relevance
“…Regarding the employment rate, people move into the business areas that are defined by higher income rates and more job opportunities [47]. Some researchers believe that the impact of population dynamics indeed comes from the city's economy and urbanisation characteristics [20,48], but some people believe that accessibility incites more changes in the population [49][50][51][52]. Research into population dynamics has also found that the population and employment rate were observed to have a higher growth rate due to HSR services [45].…”
Section: Population Dynamicsmentioning
confidence: 99%
“…Regarding the employment rate, people move into the business areas that are defined by higher income rates and more job opportunities [47]. Some researchers believe that the impact of population dynamics indeed comes from the city's economy and urbanisation characteristics [20,48], but some people believe that accessibility incites more changes in the population [49][50][51][52]. Research into population dynamics has also found that the population and employment rate were observed to have a higher growth rate due to HSR services [45].…”
Section: Population Dynamicsmentioning
confidence: 99%
“…La variación temporal de este segundo componente ha sido ignorada en la mayor parte de los estudios dinámicos de accesibilidad. La consideración conjunta de las dos fuentes de variación temporal, ya se trate de transporte público (Boisjoly y ElGeneidy, 2016) o privado (Moya-Gómez et al, 2017), ofrece resultados más realistas y permite analizar el impacto de cada uno de los dos componentes (tiempos de viaje y capacidad de atracción de los destinos) por medio de la construcción de escenarios de evaluación.…”
Section: Análisis De Accesibilidadunclassified
“…The use of new data sources enables time-sensitive accessibility analysis in ArcGIS (for recent application see Moya-Gómez et al 2017). This trend will be followed with a test implementation of General Transit Feed Specification (GTFS) data in combination with an OSM pedestrian network for the TUM Accessibility Atlas in the near future, allowing for a detailed accessibility analysis at different times of day.…”
Section: Expanding the Scope Of Analysismentioning
confidence: 99%